Encapsulation of Capacitive Micromachined Ultrasonic Transducers (CMUTs) for the Acoustic Communication between Medical Implants - Jorge Oevermann; Peter Weber; Steffen H. Tretbar (Sensors, 2021)
The aim of this work was to extend conventional medical implants by the possibility of communication between them. For reasons of data security and transmitting distances, this communication should be realized using ultrasound, which is generated and detected by capacitive micromachined ultrasonic transducers (CMUTs). These offer the advantage of an inherent high bandwidth and a high integration capability. To protect the surrounding tissue, it has to be encapsulated. In contrast to previous results of other research groups dealing with the encapsulation of CMUTs, the goal here is to integrate the CMUT into the housing of a medical implant. In this work, CMUTs were designed and fabricated for a center frequency of 2 MHz in water and experimentally tested on their characteristics for operation behind layers of Polyether ether ketone (PEEK) and titanium, two typical materials for the housings of medical implants. It could be shown that with silicone as a coupling layer it is possible to operate a CMUT behind the housing of an implant. Although it changes the characteristics of the CMUT, the setup is found to be well suited for communication between two transducers over a distance of at least 8 cm.